Figure 1 from Determinants and Effectiveness of Extending the Duration of Adjuvant Hormone Therapy beyond 5 Years in Patients with Breast Cancer - Erwei Zeng (14958443) (2025)
Flow chart of study population. Note: Extending adjuvant hormone therapy was defined as continuing the therapy for ≥6 months and filling ≥2 prescriptions of tamoxifen or aromatase inhibitors beyond the 5-year adjuvant hormone therapy.